Peningkatan Kompetensi Guru Dalam Melaksanakan Pembelajaran Melalui Kepemimpinan Transformational Kepala Sekolah Berbasis Inspirational Motivation di SDN 11/X Nipah Panjang Semester Genap Tahun Ajaran 2021/2022 - Kartini Kartini (Departement of Mathematics Education, 2023)
This research is motivated by the competence of teachers in carrying out learning that still needs to be improved. This study aims to obtain information and discuss increasing teacher competence in carrying out learning through inspirational motivation-based transformational leadership of principals at SDN 11/X Nipah Panjang even semester of the 2021/2022 academic year. This type of research is school action research. This research was conducted at SDN 11/X Nipah Panjang even semester of the 2021/2022 academic year. The research subjects were all teachers at SDN 11/X Nipah Panjang, totaling 8 people who were class I to class VI teachers and PAI teachers at SDN 11/X Nipah Panjang. Data was collected through observation sheets, field notes, and documentation. Data analysis techniques use proportions and data reduction. Based on the results of the research and discussion, it can be concluded that through inspirational motivation-based transformational leadership, principals can increase teacher competence in carrying out learning through SDN 11/X Nipah Panjang even semester of the 2021/2022 academic year by giving rewards.